2021
DOI: 10.34117/bjdv7n10-433
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional supplementation and growth after hospital discharge in very low birthweight newborns: Randomized controlled trial / Suplementação nutricional e crescimento de recém-nascidos de muito baixo peso após alta hospitalar: Ensaio clínico randomizado

Abstract: Background Evidence is insufficient to show whether fortification has any effect on growth in preterm infants after discharge. Objective to verify whether VLBW preterm infants who are supplemented with multicomponent present greater anthropometric measurements than those not supplemented. Study Design Parallel randomized controlled trial. A computer-generated random number table was used to allocate the participants. Participants Preterm infants discharged from the NICU of a University Hospital from northeast,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
(21 reference statements)
0
1
0
Order By: Relevance
“…Asia and Southern Europe showed a high LBW rate, as shown in Table 1. A previous study showed that such children have subnormal heights [22]. They have fewer educational achievements, their average age in high school education was higher, and they were enrolled in post-secondary studies at a much lower rate than their middle birth weight counterparts.…”
Section: Resultsmentioning
confidence: 98%
“…Asia and Southern Europe showed a high LBW rate, as shown in Table 1. A previous study showed that such children have subnormal heights [22]. They have fewer educational achievements, their average age in high school education was higher, and they were enrolled in post-secondary studies at a much lower rate than their middle birth weight counterparts.…”
Section: Resultsmentioning
confidence: 98%